Dental implants from functionally graded materials. Issue 10 (11th June 2013) - Mehrali, Mehdi; Shirazi, Farid Seyed; Mehrali, Mohammad; Metselaar, Hendrik Simon Cornelis; Kadri, Nahrizul Adib Bin; Osman, Noor Azuan Abu
<x xml:space="preserve">Abstract</x> Functionally graded material (FGM) is a heterogeneous composite material including a number of constituents that exhibit a compositional gradient from one surface of the material to the other subsequently, resulting in a material with continuously varying properties in the thickness direction. FGMs are gaining attention for biomedical applications, especially for implants, owing to their reported superior composition. Dental implants can be functionally graded to create an optimized mechanical behavior and achieve the intended biocompatibility and osseointegration improvement. This review presents a comprehensive summary of biomaterials and manufacturing techniques researchers employ throughout the world. Generally, FGM and FGM porous biomaterials are more difficult to fabricate than uniform or homogenous biomaterials. Therefore, our discussion is intended to give the readers about successful and obstacles fabrication of FGM and porous FGM in dental implants that will bring state‐of‐the‐art technology to the bedside and develop quality of life and present standards of care. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 3046‐3057, 2013.